The Relation Among Business Process Orientation Practices in Influencing Organizational Performance - Stefanus Christian Susetyo Harjanto; ER Mahendrawathi (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2023)
Organizations always look for ways to improve their performance to survive in the business environment. One way to improve organizational performance is to improve business process orientation (BPO). Several studies identified practices that can be implemented and significantly impact an organization’s BPO maturity. These practices are called Critical Practices (CPs) strategic view, process definition and documentation, process measurement and management, organizational process structure, people management, process organizational culture, market orientation, supplier view, and information technology. However, most studies treat CPs independently, and the relationship between CPs and between CPs with organizational performance has not been addressed. This study tests and confirms the relationship between CPs, BPO, and organizational performance. Based on the literature, a structural model of the relationship between CPs and organizational performance is developed. An online questionnaire is designed to collect data from various organizations in Indonesia. The survey results are analyzed using Structural Equation Modeling (SEM) to investigate the relationship between variables. Most hypothesized relationships between CPs are confirmed except the relationship between supplier practices (SU) and culture (CT), which are not supported. Not all practices affect organizational performance directly, but they must be mediated by other practices to have a significant effect. The results suggest that to improve organizational performance, an organization needs to improve the practice of strategic view (SV), performance measurement (PM), customer (CU), process definition (PD), and information technology (IT).